Brain Activity during Lower-Limb Movement with Manual Facilitation: An fMRI Study - Patrícia Maria Duarte de Almeida; Ana Isabel Correia Matos de Ferreira Vieira; Nádia Isabel Silva Canário; Miguel Castelo-Branco; Alexandre Lemos de Castro Caldas (Neurology Research International)
Brain activity knowledge of healthy subjects is an important reference in the context of motor control and reeducation. While the normal brain behavior for upper-limb motor control has been widely explored, the same is not true for lower-limb control. Also the effects that different stimuli can evoke on movement and respective brain activity are important in the context of motor potentialization and reeducation. For a better understanding of these processes, a functional magnetic resonance imaging (fMRI) was used to collect data of 10 healthy subjects performing lower-limb multijoint functional movement under three stimuli: verbal stimulus, manual facilitation, and verbal + manual facilitation. Results showed that, with verbal stimulus, both lower limbs elicit bilateral cortical brain activation; with manual facilitation, only the left lower limb (LLL) elicits bilateral activation while the right lower limb (RLL) elicits contralateral activation; verbal + manual facilitation elicits bilateral activation for the LLL and contralateral activation for the RLL. Manual facilitation also elicits subcortical activation in white matter, the thalamus, pons, and cerebellum. Deactivations were also found for lower-limb movement. Manual facilitation is stimulus capable of generating brain activity in healthy subjects. Stimuli need to be specific for bilateral activation and regarding which brain areas we aim to activate.